Theoretical and Experimental Studies on Elasto-Plastic Deformation of an Element with Surface Layer - Z. Handzel-Powierża; S. Kucharski; G. Starzyński (Engineering Transactions, 1996)
Comparison of analytical calculations with results of experimental measurements of stresses and strains occurring in the element with surface layer, subjected to the tension test and then unloaded, was presented. The specimens were thin-walled tubes made of copper, on which a chromium layer was galvanically laid on. The differences between the tension curves for the homogeneous specimen and the specimen with a layer, are found to be considerable even at the macroscopic level. This effect is caused by large differences in mechanical properties of the core and the layer. The comparison of the theoretical model and experimental results has shown a good agreement, up to the strain level above which cracks appear in the chromium layer. The performed experiments confirm the accuracy of the numerical programs prepared for the case of multiaxial state of stress.